Impact of School-University Partnerships and Professional Learning Communities - Adeoye, Moses Adeleke; Akinnubi, Olaolu Paul; Suleiman, Yusuf; Mahmud, Musa Aremu; Jimoh, Hassanat Abdullateef (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
School-university partnerships and professional learning communities (PLCs) are important approaches to school reform that have the potential to improve teaching and learning and improve student outcomes. School-university partnerships are collaborative relationships between schools and universities that aim to improve teaching and learning outcomes by providing access to resources and expertise and by developing new curricula and instructional materials. This study analyzes the positive impact of partnerships and communities on teaching and learning outcomes but also acknowledges the challenges they face such as time constraints, funding, and cultural differences. The research method uses Systematic Literature Review (SLR). The data collection process is carried out by identifying and evaluating scientific articles that are relevant to the topic. A literature search was conducted through academic databases, such as PubMed, ERIC, and Google Scholar. The data found analyzed to identify patterns, trends, and consistencies in the findings. Drawing on existing literature and case studies of successful partnerships found that these collaborative models have the potential to significantly improve educational outcomes for students while providing meaningful professional development opportunities for teachers. Success factors include building relationships based on mutual respect and trust, ongoing communication and collaboration and structured professional development. It was concluded that implementing partnerships will create a culture for continuous improvement within the school community.